2010
DOI: 10.1063/1.3460644
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence studies on structural defects and room temperature ferromagnetism in Ni and Ni–H doped ZnO nanoparticles

Abstract: We explore the effects of hydrogenated annealing on the crystal structure, room temperature ferromagnetism (RT-FM) and photoluminescence (PL) properties of Ni-doped ZnO (Zn1−xNixO, x=0.0 to 0.2) nanoparticles prepared by a sol-gel method. The x-ray photoelectron spectra and x-ray diffraction data provide evidence that Ni has been incorporated into the wurtzite ZnO lattice as Ni2+ ions substituting for Zn2+ ions at x≤0.05. A secondary phase of NiO type begins to form inside ZnO when x>0.05 and segregates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 48 publications
3
26
0
Order By: Relevance
“…The similar trend of change in 2θ value after Ni doping was reported by Yu et al 34 and Tong et al 35 From the interplanar spacing obtained XRD used to estimate the lattice parameters. The (002) plane XRD peak was used for the grain size calculation and the results are shown in table I. properties of ZnO, which we already discuss in the previous report 4 .…”
Section: +supporting
confidence: 54%
“…The similar trend of change in 2θ value after Ni doping was reported by Yu et al 34 and Tong et al 35 From the interplanar spacing obtained XRD used to estimate the lattice parameters. The (002) plane XRD peak was used for the grain size calculation and the results are shown in table I. properties of ZnO, which we already discuss in the previous report 4 .…”
Section: +supporting
confidence: 54%
“…Seehra et al [38], on the other hand suggested that the CuO phase is paramagnet in the Cu x Zn 1−x O/CuO composite. Tong et al [39], and Wang et al [40] showed, that hydrogen incorporation in the sample can induced ferromagnetism. They believed, that hydrogen as shallow donor might be responsible for the enhancement of RTFM.…”
Section: Resultsmentioning
confidence: 99%
“…UV and Visible bands in undoped and doped ZnO have multiple emission and frequently assigned to differentiate defects. 38 UV emission (i.e., NBE) region $350-450 nm of some selected samples, e.g., y ¼ 0, 0.06, and 0.10 samples is enlarged for convenience and can be well fitted by two Gaussian lineshape peaks shown Figs. 6(a)-6(c), respectively.…”
Section: B Photoluminescence Spectroscopymentioning
confidence: 99%